Tanggung Jawab Hukum PT. Gojek Indonesia Atas Hilangnya Saldo Go-Pay Konsumen Dalam Layanan Go-Food - Rahmadi Indra Tektona; Dyah Ochtorina Susanti; Nurhayati Nurhayati (Universitas Widya Gama Malang, 2020)
This research was conducted to analyze the legal issues regarding the legal responsibility of PT. Gojek Indonesia for consumer losses due to loss of Go-Pay balance in the Gojek account when using the Go-Food service. The type of research used by the author is the type of normative juridical assessment. Then the method used is the law approach and conceptual approach. Whereas the source of legal material consists of:/ a.) Primary legal material, namely laws, and regulations; b.) Secondary legal material includes law books, legal journals, and scientific works in the field of law c.) Non-legal material in the form of information from the internet relating to the science of law related to the problem being studied. Analysis of the legal material used is to use the method of deductive analysis, which is a method of things that are general towards specific things. The results of the research on PT. Gojek Indonesia in the event of loss of consumer balance is liability based on an element of error. PT. Gojek Indonesia as the manager of the Gojek application is obliged to bear consumer losses by providing compensation in the form of returning a sum of money or replacing a lost amount